5 - 4 + 7x + 1 = 7x + (5 - 4 + 1) = 7x + 2
NO SOLUTIONS:
<em>5 - 4 + 7x + 1 = 7x + a </em><em>(a - any real number, except 2)</em>
ONE SOLUTION:
<em>5 - 4 + 7x + 1 = bx + c </em><em>(b - any real number, except 7, c - any real number)</em>
INFINITELY MANY SOLUTIONS:
<em>5 - 4 + 7x + 1 = 7x + 2</em>
Examples:
2x + 3 = 2x + 5 <em>subtract 2x from both sides</em>
3 = 5 FALSE <em>(NO SOLUTIONS)</em>
2x + 3 = x - 4 <em>subtract x from both sides</em>
x + 3 = -4 <em>subtract 3 from both sides</em>
x = -7 (<em>ONE SOLUTION)</em>
2x + 3 = 2x + 3 <em>subtract 2x from both sides</em>
3 = 3 TRUE <em>(INFINITELY MANY SOLUTIONS)</em>
Answer:
8 a b - 4 a + 3 b + 16. Simplify: 8 a b - 4 a + 3 b + 16 Answer: 8 a b - 4 a + 3 b + 16
Coefficient is any of the factors with the sign of the term. ... The given algebraic expression has three terms, namely, 4a 4b2c – 3a3b2c and 3/2 ab3c2
Step-by-step explanation:
Answer:
The answer to x2=25 is x=5
Step-by-step explanation:
When using factoring to solve this problem I just square rooted both numbers. The square root of x2 is x and the square root of 25 is 5. Sorry i couldn't help with all of them!
Step-by-step explanation:
x + 6 = 2x - 8
1. Subtract 2x from both sides
x - 2x + 6 = 2x - 2x - 8
2. Simplify
-x + 6 = -8
3. Now, subtract 6 from both sides
-x + 6 - 6 = -8 - 6
4. Simplify
-x = -14
5. Divide both sides by -1 because you would want the x by itself instead of having -x
-1x/-1 = -14/-1
6. Simplify
x = 14 <------ Answer
Hope that helped!!
~Shane
Answer:
39,088?
Step-by-step explanation: